HUBUNGAN KADAR LOWDENSITY LIPOPROTEIN CHOLESTEROL DENGAN KEJADIAN DAN KEPARAHAN STROKE AKUT - Azwita Effrina Hasibuan*, Aida Fitri*, Khairul Putra Surbakti*, Aldy Safruddin Rambe* (Neurona Majalah Kedokteran Neuro Sains, 2015)
INTRODUCTION THE ROLE OF SERUM CHOLESTEROL IN STROKE ETIOLOGY IS STILL UNCERTAIN STUDIES FOCUSING ON ASSOCIATION BETWEEN LOWDENSITY LIPOPROTEIN LDL CHOLESTEROL AND ACUTE STROKE ARE STILL RARE AND INCONSISTENT